(untitled) (Veterinary Science, 2017)
In the present work a serologic survey in rearing hens and layer hens, older than twelve weeks of age, was carried out with the purpose of determinig prevalent antibodies against Salmonella sp. The study was fulfilled in the departaments Capital, Conhelo, Chapaleufú and Maracó of the Province of La Pampa, by means of the PQA technique, finding in such studies that the prevalence for the infection in the group of layer hens is of 5.9% and in the rearing hens is of 3%